Iatrogenic ureteral injury during laparoscopic versus open colectomy - Ayman M. Abdulmohaymen (Al-Azhar Assiut Medical Journal)
Background and aim The rate of iatrogenic ureteral injury varies greatly depending on surgical approach and experience of the surgical team. This study compares laparoscopic and open colectomy regarding incidence of ureteral injury. Methods This double-blind prospective study was performed on 120 patients undergoing colectomy. Patients were divided in group A (laparoscopic) and group B (open). Both groups were compared regarding incidence of iatrogenic ureteral injury. Results A total of 41 patients were in group A and 79 were in group B. One case of ureteral injury was identified during laparoscopic and another was identified during open procedures. Incidence of iatrogenic ureteral injury in laparoscopic group was 2.4% compared with 1.2% in open colectomy cases. Conclusion There is no statistically significant difference between its incidence in laparoscopic colectomy and open colectomy. Therefore, laparoscopic colectomy is a safe alternative to open colectomy with regard to iatrogenic ureteral injury.